Chemotherapy induces feedback up-regulation of CD44v6 in colorectal cancer initiating cells through β-catenin/MDR1 signaling to sustain chemoresistance - Ghatak, Shibnath; Hascall, Vincent C.; Karamanos, Nikos; Markwald, Roger R.; Misra, Suniti (Frontiers in Oncology, 2022)
ABSTRACT Chemoresistance in colorectal cancer initiating cells (CICs) involves the sustained activation of multiple drug resistance (MDR) and WNT/β-catenin signaling pathways, as well as of alternatively spliced-isoforms of CD44 containing variable exon-6 (CD44v6). In spite of its importance, mechanisms underlying the sustained activity of WNT/β-catenin signaling have remained elusive. The presence of binding elements of the β-catenin-interacting transcription factor TCF4 in the MDR1 and CD44 promoters suggests that crosstalk between WNT/β-catenin/TCF4-activation and the expression of the CD44v6 isoform mediated by FOLFOX, a first-line chemotherapeutic agent for colorectal cancer, could be a fundamental mechanism of FOLFOX resistance. Our results identify that FOLFOX treatment induced WNT3A secretion, which stimulated a positive feedback loop coupling β‐catenin signaling and CD44v6 splicing. In conjunction with FOLFOX induced WNT3A signal, specific CD44v6 variants produced by alternative splicing subsequently enhance the late wave of WNT/β-catenin activation to facilitate cell cycle progression. Moreover, we revealed that FOLFOX-mediated sustained WNT signal requires the formation of a CD44v6-LRP6-signalosome in caveolin microdomains, which leads to increased FOLFOX efflux. FOLFOX-resistance in colorectal CICs occurs in the absence of tumor-suppressor disabled-2 (DAB2), an inhibitor of WNT/β-catenin signaling. Conversely, in sensitive cells, DAB2 mediated suppression of WNT-signaling requires interaction with a clathrin containing CD44v6-LRP6-signalosome. Furthermore, full-length CD44v6, once internalized through the caveolin-signalosome, is translocated to the nucleus where in complex with TCF4, it binds to β-catenin/TCF4-regulated MDR1, or CD44 promoters, which leads to FOLFOX-resistance and CD44v6 transcription through transcriptional-reprogramming. These findings provide evidence that targeting CD44v6-mediated LRP6/β-catenin-signaling and drug efflux may represent a novel approach to overcome FOLFOX resistance and inhibit tumor progression in colorectal CICs. Thus, sustained drug resistance in colorectal CICs is mediated by overexpression of CD44v6, which is both a functional biomarker and a therapeutic target in colorectal cancer.